Practice in industry training in fish culture - Montoya, Teresita P. (College of Fisheries, University of the Philippines, 1954)
This report embody practically all the things that was learned and done by me during the six months stay in Dagat-dagatan experimental station, both practical and research work pertaining to fisheries. In order to accomplish of what to be expected of us in this course the six months practice-in-industry has been the policy of the Philippine institute of fisheries technology as an important requirement for graduation. The significance of this study was the application of the principles learned during the two years of theoretical subjects. Moreover, the experiences and observation and the various important phases of the activities undertaken in fishponds and experimental station are also treated in this report of mine. It is also in this training where we learned fishpond management specially the managing of fertilized fishponds which were undertaken at the time when I took my apprenticeship in this station. So I considered my self-fortunate because in the fertilization of the fishponds it was not given to us in our two years course. I can also say that this practical training is a great opportunity for the students to learn more knowledge and experiences regards to fishponds management.